2018
DOI: 10.5380/abclima.v23i0.60406
|View full text |Cite
|
Sign up to set email alerts
|

Determinação De Regiões Homogêneas De Precipitação Pluviométrica No Estado Do Paraná Por Meio De Técnicas De Análise Multivariada E Geoestatística

Abstract: Tendo em vista a importância regional da precipitação pluviométrica como variável climática que mais impacta as principais atividades humanas, este trabalho objetivou identificar e determinar regiões homogêneas dos padrões pluviométricos no Estado do Paraná. Para tanto, utilizou-se técnicas multivariadas de análise de componentes principais e análise de agrupamento, bem como métodos geoestatísticos para espacialização de séries pluviométricas georreferenciadas de 49 estações meteorológicas distribuídas pelo Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The areas of high or intermediate rainfall in the eastern portion and at specific points north of the hydrographic region, harmonized with the C3 cluster. This agreement between homogeneous zones and the annual rainfall distribution was also obtained by other authors (DOURADO et al, 2013;GEBERT et al, 2018). Dourado et al (2013) identified homogeneous rainfall zones for the entire state of Bahia, using an algorithm different from that of Ward (1963).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The areas of high or intermediate rainfall in the eastern portion and at specific points north of the hydrographic region, harmonized with the C3 cluster. This agreement between homogeneous zones and the annual rainfall distribution was also obtained by other authors (DOURADO et al, 2013;GEBERT et al, 2018). Dourado et al (2013) identified homogeneous rainfall zones for the entire state of Bahia, using an algorithm different from that of Ward (1963).…”
Section: Resultssupporting
confidence: 83%
“…Figure 9 shows the dendrogram representing the similarity between the precipitation of the stations effectively inserted in Paraguaçu. Considering that the level of similarity does not increase significantly for less variation in the Euclidean distance, the cut-off criterion was adopted where the number n of groups formed results from the greatest amplitude in relation to the subsequent n+1, the same criterion adopted by Singh et al (2017) and Gebert et al (2018). Thus, as the greatest amplitude of Euclidean distance was observed in the migration from three to four groups, three groupings were the quantity adopted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation